Sinergitas Pos UKK, Gapoktan, Desa dan Puskesmas Dalam Mewujudkan Desa Safety Farming - Eka Rosanti; Ratih Andhika Akbar Rahma; Mahmudah Hamawi (Universitas Muhammadiyah Surakarta, 2022)
The farmer’s behavior in Demangan Village is not safe and healthy in carrying out agricultural activities especially on pesticide use starting from mixing, spraying, washing the equipment and dispose the pesticide bottles. Therefore, efforts are needed to form a safe farming village in three years by involving two partners, they were the Pos UKK Demang Jaya Sehat and Gapoktan Demang Jaya. In the third year, the partners have not been able to carry out the work program independently, the synergy with the government and community health center is needed. The community service team helps activities through the FGD method and assistance with partners, governments, and community health centers. At the end of the activity, an evaluation of the achievements and obstacles to be followed up. Based on the activities that have been carried out, the government and community health centers contribute to the partner’s work program such as fulfilling facilities (utilization of village halls for meetings, crooked land for planting lemongrass, and BUMDES for the operation of Pos UKK and sales citronella oil), funding (purchase of materials and completeness of RSBP), human resources (assistance, monitoring, education, and active participation), and administration (data provision). So partners can carry out work programs properly, the role of the Pos UKK as implementing basic health services and Gapoktan as organic farming actors. Synergy is needed to maintain program sustainability.